The Timing and Magnitude of the Type I Interferon Response Are Correlated with Disease Tolerance in Arbovirus Infection - Alexandra Hardy; Siddharth Bakshi; Wilhelm Furnon; Oscar MacLean; Quan Gu; Margus Varjak; Mariana Varela; Muhamad Afiq Aziz; Andrew E. Shaw; Rute Maria Pinto; Natalia Cameron Ruiz; Catrina Mullan; et al. (mBio, 2023)
ABSTRACT Infected hosts possess two alternative strategies to protect themselves against the negative impact of virus infections: resistance, used to abrogate virus replication, and disease tolerance, used to avoid tissue damage without controlling viral burden. The principles governing pathogen resistance are well understood, while less is known about those involved in disease tolerance. Here, we studied bluetongue virus (BTV), the cause of bluetongue disease of ruminants, as a model system to investigate the mechanisms of virus-host interactions correlating with disease tolerance. BTV induces clinical disease mainly in sheep, while cattle are considered reservoirs of infection, rarely exhibiting clinical symptoms despite sustained viremia. Using primary cells from multiple donors, we show that BTV consistently reaches higher titers in ovine cells than cells from cattle. The variable replication kinetics of BTV in sheep and cow cells were mostly abolished by abrogating the cell type I interferon (IFN) response. We identified restriction factors blocking BTV replication, but both the sheep and cow orthologues of these antiviral genes possess anti-BTV properties. Importantly, we demonstrate that BTV induces a faster host cell protein synthesis shutoff in primary sheep cells than cow cells, which results in an earlier downregulation of antiviral proteins. Moreover, by using RNA sequencing (RNA-seq), we also show a more pronounced expression of interferon-stimulated genes (ISGs) in BTV-infected cow cells than sheep cells. Our data provide a new perspective on how the type I IFN response in reservoir species can have overall positive effects on both virus and host evolution. IMPORTANCE The host immune response usually aims to inhibit virus replication in order to avoid cell damage and disease. In some cases, however, the infected host avoids the deleterious effects of infection despite high levels of viral replication. This strategy is known as disease tolerance, and it is used by animal reservoirs of some zoonotic viruses. Here, using a virus of ruminants (bluetongue virus [BTV]) as an experimental system, we dissected virus-host interactions in cells collected from species that are susceptible (sheep) or tolerant (cow) to disease. We show that (i) virus modulation of the host antiviral type I interferon (IFN) responses, (ii) viral replication kinetics, and (iii) virus-induced cell damage differ in tolerant and susceptible BTV-infected cells. Understanding the complex virus-host interactions in disease tolerance can allow us to disentangle the critical balance between protective and damaging host immune responses.